In vitro efficacy of bacterial endophytes against the chilli damping-off pathogen Pythium aphanidermatum - MUTHUKUMAR, Arjunan; NAKKEERAN, Sevugapperumal; ESWARAN, Ayyadurai; SANGEETHA, Ganesan (Phytopathologia Mediterranea, 2010)
Damping-off of chilli caused by Pythium aphanidermatum is a major nursery disease in vegetables. The effect of ten endophytic isolates of Pseudomonas fluorescens was tested against P. aphanidermatum under in vitro conditions. All the isolates tested were short rods and produced bright fluorescence when exposed to UV light. Among the isolates, EBS 20 produced the largest inhibition zone and the least mycelial growth of P. aphanidermatum. With regard to the secondary metabolites, P. fluorescens EBS 20 produced most salicylic acid, siderophore and hydrogen cyanide. The culture filtrate of this isolate at a 15% concentration totally inhibited mycelial growth of P. aphanidermatum. In addition, chilli seeds treated with culture filtrate of this isolate also led to the greatest plant growth in terms of root length, shoot length and vigour index.